2014
DOI: 10.1118/1.4866889
|View full text |Cite
|
Sign up to set email alerts
|

The influence of respiratory motion on CT image volume definition

Abstract: Respiratory 4DCT images provide accurate volume and position of organs affected by breath motion detecting higher volume discrepancies as amplitude length or breath frequency are increased. For 3DCT acquisitions, a CT should be considered slow enough to include lesion envelope as long as the slice acquisition time exceeds twice the breathing period. If this requirement cannot be satisfied, a fast CT (along with breath-hold inhale and exhale CTs to estimate roughly the ITV) is recommended in order to minimize s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…This emphasizes the need for either larger internal margins, if tumour volumes are delineated on the MIP (or AIP) data set or contouring on all 10 phases for particular cases (lower lobe and/or smaller tumour volume). This is similar to the findings of Ezhil et al [39], who concluded that the MIP volume underestimates tumour volume changes, and to the findings of Romero et al [40], who stated that the tumour volume variations can exceed 5% for object dimension 1 cm. Nakamura et al [37] concentrated more on the tumour motion range and recommended additional internal margins even for the lung tumours with a motion range of 0.8 cm or less.…”
Section: Discussionsupporting
confidence: 91%
“…This emphasizes the need for either larger internal margins, if tumour volumes are delineated on the MIP (or AIP) data set or contouring on all 10 phases for particular cases (lower lobe and/or smaller tumour volume). This is similar to the findings of Ezhil et al [39], who concluded that the MIP volume underestimates tumour volume changes, and to the findings of Romero et al [40], who stated that the tumour volume variations can exceed 5% for object dimension 1 cm. Nakamura et al [37] concentrated more on the tumour motion range and recommended additional internal margins even for the lung tumours with a motion range of 0.8 cm or less.…”
Section: Discussionsupporting
confidence: 91%
“…[8][9][10]12,14 This study presented length changes to allow better estimations of the margins expected if all phases are used for target definition in building an ITV or for treatment using 4D-VMAT. 6 Indeed, it has recently been shown that the MIP may not be adequate in defining the target for the oesophagus, 15 and therefore an increasing amount of information is required for target definition across all phases.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration-induced tumor motion increases safety margins around the target volume, resulting in the irradiation of a considerable volume of surrounding noncancerous tissue. [1][2][3] Thus, tumor motion management is needed to allow higher doses to the tumor while sparing healthy tissue. In recent years, many studies have investigated various aspects of tumor motion management and developed different kinds of tools to compensate tumor motion during radiation therapy.…”
Section: Introductionmentioning
confidence: 99%